A new species of simulium (gomphostilbia) (Diptera: Simuliidae) from Thailand, with keys to 11 species of the simulium varicorne species-group - Hiroyuki Takaoka (2018)
ABSTRACT Simulium (Gomphostilbia) piroonae sp. nov. is described on the basis of females, males, pupae, and mature larvae collected in Mae Hong Son Province, Thailand. This new species is placed in the chumpornense subgroup of the varicorne species-group in the subgenus Gomphostilbia by having the antenna with eight flagellomeres, the pleural membrane bare, the female subcosta lacking hairs, and the pupal gill basally divided into two somewhat inflated branches. It is distinguished from all 10 known species of this group by the pupal gill with six filaments. Keys to identify 11 species of the varicorne species-group are provided for females, males, pupae, and mature larvae.